THE ROLE OF PARENTS IN EDUCATING CHILDREN IN THE DIGITAL AGE - Apdillah, Dicky; Simanjuntak, Cici Rahma Alia; Napitupulu, Celly Naomi Sarah Br; Sirait, Deviana Dewi; Mangunsong, Juliana (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2022)
Technological advancements are becoming increasingly pervasive in daily life. Children develop at a rapid pace as technology advances, from televisions to computers, smartphones, and digital tablet devices equipped with a variety of applications. Today's children, called by “Generation Alpha," are markedly different from prior generations. They spend the most of their time interacting with digital technologies. Because technology pervades both parents' and children's lives, there is concern over its negative impact on very young children's cognitive, motor, and social development. According to research, parents play the most critical role in establishing a child-friendly atmosphere. The schedule that parents follow with their children is designed to meet the child's physical and psychological needs. Additionally, this pattern can be implemented through socialization of societal norms, allowing youngsters to live in harmony with their environment. As a matter of fact, parents must be capable of educating and guiding children in the ethical and positive use of digital media.